2007
DOI: 10.1002/cncr.22973
|View full text |Cite
|
Sign up to set email alerts
|

Preventing pain during office biopsy of the prostate

Abstract: Leaf protein concentrates (LPC) can be used as a valuable co‐product to cellulosic biofuel production and can also mitigate the food versus fuel controversy. Two major approaches have been considered for LPC production: a well‐characterized mechanical pressing method and a less studied method involving aqueous extraction with recovery using ultrafiltration. Experimental results with switchgrass extracts show low protein recovery after filtration, particularly if protein is recovered after cellulose hydrolysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, periprostatic infiltration of the anesthetic is not a painless procedure in itself (1,2,3,4). Ashley et al (2) reported that this was the most painful part of the procedure. In this study, pain produced by injection was higher in amplitude than the biopsy pain measured at the time when the patient was under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, periprostatic infiltration of the anesthetic is not a painless procedure in itself (1,2,3,4). Ashley et al (2) reported that this was the most painful part of the procedure. In this study, pain produced by injection was higher in amplitude than the biopsy pain measured at the time when the patient was under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Transrectal ultrasound (TRUS)-guided prostate biopsy is a standard method in the diagnosis of prostate cancer. Although minimally invasive, it is not a painless procedure (1,2,3,4). Procedure-related pain especially occurs due to placement of the probe in the anal canal, movement of the probe and penetration of the needle to the prostate during biopsy (5).…”
Section: Introductionmentioning
confidence: 99%
“…There are established factors that influenced experience of severe pain during TRUS guided prostate biopsy; age, [6] prostate volume, [7] number of biopsy core samples, [8] sampling site [9] and pre biopsy anxiety which occurs in 67% of patients resulting in exaggerated pain perception [10][11][12] , have all been reported as significant predictors of pain. The intensity of pain felt during prostate biopsy maybe ascribed to activities performed prior to biopsy which include digital rectal examination, insertion of ultrasound probe in TRUS-guided prostate biopsy or insertion of needles in to the rectum during peri-prostatic block [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The European Association of Urology recommend topical anesthesia plus periprostatic nerve bundle block (PPNB) [10]; however, there are multiple trials considering other approaches like a single PPNB, only topical gels, combined therapies, among others, additionally, there is some evidence supporting that the most painful moment is the application of the anesthetic [10, 11].…”
Section: Introductionmentioning
confidence: 99%